Sex differences among patients receiving ticagrelor monotherapy or aspirin after coronary bypass surgery: A prespecified subgroup analysis of the TiCAB trial. (1st January 2023) - Sandner, Sigrid; Kastrati, Adnan; Niessner, Alexander; Böning, Andreas; Zeymer, Uwe; Conradi, Lenard; Danner, Bernhard; Zimpfer, Daniel; Färber, Gloria; Manville, Emely; Schunkert, Heribert; von Scheidt, Moritz; et al.
Abstract: Background: There is limited evidence on the association of sex with outcomes among patients undergoing coronary bypass surgery (CABG) and treated with ticagrelor monotherapy or aspirin. Methods: This was a pre-specified sub-analysis of TiCAB, an investigator-initiated placebo-controlled randomized trial. Primary efficacy endpoint was the composite of cardiovascular death, myocardial infarction, stroke, or repeat revascularization 1 year after CABG. Safety endpoint was BARC type 2, 3 or 5 bleeding. Results: A total of 280 (15.0%) women and 1579 (85.0%) men were included. Compared with men, women were older (66.1 ± 10.2 vs. 70.1 ± 9.3 years) with more acute presentation (17.0% vs 21.1%). The incidence of the primary endpoint was similar between women and men (9.2% vs. 8.9%, HR 1.08, 95%CI 0.71–1.66, P = 0.71). Cardiovascular death occurred more often in women (2.9% vs 1.0%, adjusted HR 2.87, 95%CI 1.23–6.70, P = 0.02). The incidence of bleeding was similar between the sexes (2.2% vs. 2.5%, HR 0.91, 95% CI 0.51–1.65, P = 0.77). Ticagrelor vs aspirin was associated with a similar risk of the primary endpoint in women (10.6% vs. 7.9%, HR 1.39, 95%CI 0.63–3.05, P = 0.42) and men (9.5% vs. 8.2%, HR 1.15, 95%CI 0.82–1.62, P = 0.41;pinteraction = 0.69), and a similar risk of bleeding in women (2.9% vs. 1.4%, HR 2.09, 95%CI 0.38–11.41, P = 0.40) and men (2.2% vs. 2.8%, HR 0.80, 95%CI 0.42–1.52, P = 0.49;pinteraction = 0.35). Conclusions: Among women and men undergoing CABG, ticagrelor monotherapy was associated with a similar risk of the primary efficacy endpoint and bleeding compared with aspirin. The risk of cardiovascular death was increased in women irrespective of antiplatelet therapy. Highlights: There are significant baseline risk differences between women and men undergoing CABG. Ticagrelor and aspirin were associated with a similar risk of CV death, MI, stroke, or revascularization in women and men. Ticagrelor and aspirin were associated with a similar risk of clinically important bleeding events in women and men. Women had a higher risk of CV death 30 days and 1 year after CABG irrespective of type of antiplatelet therapy.